New method for determination of diffraction light pattern of the arbitrary surface. (1st May 2017) - Stevanovic, N.; Markovic, V.M.; Nikezic, D.
Abstract: Diffraction phenomena have a special importance in optics. Due to their complex nature, diffraction problems cannot be solved exactly using an analytical approach for the general case. Problems for which an exact analytical solution can be found are reduced to simple ones, with a great deal of symmetry of obstacles and slits where the diffraction occurs. On the other hand, numerical methods can be very useful in solving particular problems where parameters of obstacles or slits are known. These methods can be applied in cases when the screen is at a short distance (Fresnel diffraction) as well as at a large distance (Fraunhofer diffraction). In this paper, the methodology for finding a solution in case of diffraction problem on arbitrary objects which are at an arbitrary distance from the screen is presented. The method is based on numerical solving of the Fresnel-Kirchhoff integral by means of discretization of an obstacle and the screen on which the diffraction pattern is observed. This method can be applied for arbitrary shapes of slits for which the equation of the surface is known as well as for an arbitrary positioned screen, located even very close to the object. The developed method is employed to determine the diffraction pattern for obstacles for which the pattern is already known from the theory. Good agreement was found. Highlights: The method for determination of diffraction pattern was developed. Developed method can be applied for arbitrary 3D surface. It was considered on circle, rectangular, conical and spherical surface. These results have good agreement with published in papers. That method can be applied for tracks in SSNTD, fibers.